Comportamento de fratura de coroas cerâmicas à base de zircônia submetidas ao jateamento com diferentes tamanhos de partícula - Mosele, João Cézar (2014)
The objective of this study was to investigate the fracture load and failure mode of yttrium partially stabilized tetragonal zirconia polycrystalline ceramic (Y-TZP) prosthetic crowns subjected to sandblasting with alumina particles with different sizes. Sixty Y-TZP frameworks were produced using CAD-CAM technology (Vita Inceram YZ) and veneered with porcelain (Vita VM9). Crowns were randomly divided into three groups (n=20), according to the alumina particle size used for sandblasting: (GC) no treatment (control); (G53) 53 μm alumina particles; (G125) 125 μm alumina particles. Sandblasting was performed with 0.25 MPa pressure at 10 mm distance, for 10 s. Crowns were adhesively cemented over a resin glass-reinforced die. All crowns were loaded until fracture by a stainless steel sphere, in a 37o distilled water bath, using a universal testing machine. Fracture surfaces were analyzed with a stereomicroscope. Surface roughness was evaluated using an optical perfilometer (n=5). Results were statistically analyzed by ANOVA and Tukey s test (=0.05). Reliability was accessed through Weibull analysis. G125 showed higher mean fracture load than the control group. G125 and G53 presented similar fracture load values. There were no significant differences between groups for Weibull modulus (m) and characteristic strength (0). Roughness parameters were also similar among groups. It was observed, approximately, 40% of catastrophic failures and 60% of chipping. There was no relation between failure mode and experimental group. It was concluded that the particle size had no influence on the fracture load, failure mode, reliability and surface roughness of Y-TZP crowns